The Analysis of Translation Technique and Quality in Translating Meme Image - Romita, Romita; Sujatmiko, Sujatmiko (English Language Education Department, Universitas Kristen Duta Wacana (UKDW), Yogyakarta, Indonesia, 2025)
This study aimed to find (1) the translation techniques applied by students in translating meme images, (2) the translation quality of translating meme images and (3) the student problems in translating meme images. This research used a qualitative with case study approach, and the data collection was done by content analysis, Focus Group Discussion (FGD) and interview, so that it could explore more deeply related problems found at English Department at Universitas PGRI Yogyakarta. The subjects of this research were 27 fourth semester students. The results of this study showed that the students applied 9 types of translation techniques to meme images, namely established equivalent, pure borrowing, addition, modulation, generalization, natural borrowing, explicitation, literal translation, and description. The results of the Focus Group Discussion (FGD) with experts showed that the quality of the translations of meme images by the students was 2,44 (less accurate), 2,54 (less acceptable) and 2,78 (readable). The interviews with 10 students showed that the problems in translating meme images were lack of vocabulary, confusion with meme images and not understanding the context. It was concluded that the translation techniques applied by the students contributed to the quality of the translation. The description technique contributed negatively to the accuracy of meme image translation, while the addition technique contributed negatively to the acceptability, and the established equivalent technique contributed positively to the readability in meme image translation.